Mapping the organisational and interventional framework for patients admitted to Hospital-at-Home for acute illness in Scandinavia – a scoping review protocol - Kristina Kock Hansen; Maria Klitgaard Christensen; Christian Backer Mogensen; Peter Biesenbach; Jette Holt; Pia Lysdal Veje; Mette Elkjær; Caroline Moos (PLoS ONE, 2025)
Hospitals in Scandinavia increasingly face an enormous pressure to manage acute emergencies in adults affected by multimorbid disabling conditions and therefore at risk of developing adverse hospitalisation outcomes such as nosocomial diseases. In this context, there is a growing political interest in the region to develop alternative models of acute emergency care such as the Hospital-at-Home (HaH), all the more so as adult patients themselves are showing a pronounced interest in HaH. We are therefore planning a scoping review, following the methodology proposed by Joanna Briggs Institute (JBI), to map the HaH components and interventions delivered to patients when managing acute emergencies in adults with that hospitalization model. We will search the databases MEDLINE, Embase and CENTRAL (Cochrane Central Register of Controlled trials) to include articles of studies on adults admitted to HaH for acute emergency care within 24 hours of getting in touch with either an adult emergency department, an out-of-hours doctor, or a general practitioner. No limitation will be placed on the search period. The electronic search will be supplemented by a grey literature search of ClinicalTrials.gov and of the archives of Ministries of Health of the Scandinavian region. The information recorded during the data extraction process will include study characteristics, participants characteristics and main review outcomes (interventions and organisational structures). Data will be synthesized narratively. This protocol has been registered with Open Science Framework (https://doi.org/10.17605/OSF.IO/K7NJS). Mapping data on HaH for the care of adult acute emergencies in Scandinavia will help provide Scandinavian healthcare stakeholders with an overview of the strengths and weaknesses of different existing HaH models so that they can they can integrate that knowledge to make context-specific recommendations about and subsequently formally implement the management of adult acute emergencies in HaH in the region. Ethical approval was not required as the study does not involve human participants. Findings will be submitted for publication in a peer-reviewed Scandinavian journal and disseminated through institutional websites and LinkedIn. Results will be presented at an international conference.